Business in Genocide: Understanding and Avoiding Complicity - Nora Stel; Wim Naudé (Institute for the Study of Labor (IZA), 2016)
Genocides and mass atrocities do not arise spontaneously, but tend to be meticulously sourced and managed. As such the concern in this paper is with the role of businesses in these processes, with a particular focus on the agency and decision making of entrepreneurs and managers. We critically explore the specific role entrepreneurs and businesses played in three of the most uncontested genocides of recent history: the Jewish, Kurdish, and Darfurian genocides. From this literature we seek to distill key insights into what entrepreneurs and socially responsible businesses can do to lessen the tensions, misunderstandings, exclusions, and marginalization that are among the complex causes of genocides and other mass atrocities. In order to better understand the complicity of business there is a need for a shift from diagnostic attention on how businesses are engaged in genocide to a more analytical exploration of why businesses have made the choices they did in the process of their engagement with genocide. This is also necessary to advance the debate on how to hold businesses accountable for gross human rights violations and moreover to provide incentives for businesses not only to avoid doing harm but also to proactively, preventively strive to protect and extend human rights.
Keywords: D74; O19; L26; N40; M14; 330; business; entrepreneurship; genocide; mass killings; conflict; development